An evaluation of the implementation of study-from-home policy in senior high school during Covid-19 pandemic - Simangunsong, Junus; Mustikaningsih, Hastuti (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2022)
The increase in Coronavirus Disease-19 in Indonesia has prompted the central and regional governments to issue a study-from-home (SFH) policy through the Minister of Education and Culture Circular Letter Number 4 of 2020. The policy aims to reduce activities in schools but uses a meaningful curriculum. The purpose of the evaluation is to see the SFH policy implementation related to teaching and learning activities. The collection of information and data, interviews, and group discussion forums were conducted through online meetings, including video conferencing and other social media. This policy implementation was analyzed in the aspects of context, input, process, and product. The study involved 2,862 respondents, consisting of 60 people from the Education Office, 284 school principals, 861 teachers, 677 students' parents, and 980 students. Evaluation results for each aspect show that: (1) in terms of context, policymakers in the regions have followed up Governor's decrees and the SFH program (78.33%); (2) in terms of input, schools have prepared 17% of infrastructure and the level of teacher ability is 41.64%; (3) in terms of process, 49.56% of learning is carried out online; and (4) in terms of product, 88% teachers have assessed learning outcomes. Thus, the SFH policy has been carried out optimally, but some learning factors are not going well due to limited cell phones, low teacher competence in using applications, and unavailability of the Internet network in some schools. The SFH implementation at the provincial government level has been carried out effectively and efficiently, but in schools, online learning is still found to be uneven.